Penerapan Sistem Informasi Posyandu dan Pemantuan Stunting pada Posyandu Indah Sari Kelurahan Manyaran Kota Semarang - Hartono, Budi; Lusiana, Veronica; Wahyuni, Sri; Supriyanto, Aji (Fakultas Teknologi Informasi dan Industri Unisbank, 2023)
Integrated service posts (Posyandu) are the government's efforts to make it easier for Indonesian people to obtain maternal and child health services. The main activity of posyandu is to record and monitor the nutritional status, growth and development of toddlers. Mitra Posyandu